Long-term exposure to air pollutants from multiple sources and mortality in an industrial area: a cohort study. Issue 1 (14th September 2018) - Bauleo, Lisa; Bucci, Simone; Antonucci, Chiara; Sozzi, Roberto; Davoli, Marina; Forastiere, Francesco; Ancona, Carla
Abstract : Background and aims: Residents near industrial areas are exposed to several toxins from various sources and the assessment of the health effects is difficult. The area of Civitavecchia (Italy) has several sources of environmental contamination with potential health effects. We evaluated the association between exposure to pollutants from multiple sources and mortality in a cohort of people living in the area. Methods: All residents of the area in 1996 were enrolled (from municipal registers) and followed until 2013. Long-term exposures to emissions from industrial sources (PM10) and traffic (NOx ) at the residential addresses were assessed using a dispersion model. Residence close to the harbour was also considered. Cox survival analysis was conducted including a linear term for industrial PM10 and NOx exposure and a dichotomous variable to indicate residence within 500 m of the harbour. Age, sex, calendar period, occupation and area-based socioeconomic position (SEP) were considered (HRs, 95% CI). Results: 71 362 people were enrolled (52% female, 43% low SEP) and 14 844 died during the follow-up. We found an association between industrial PM10 and mortality from non-accidental causes (HR=1.06, 95% CI 1.01 to 1.12), all cancers (HR=1.11, 95% CI 1.01 to 1.21) and cardiac diseases (HR=1.12, 95% CI 1.01 to 1.23). We also found an association between NOx exposure from traffic and mortality from all cancers (HR=1.13, 95% CI 1.01 to 1.26) and neurological diseases (HR=1.50, 95% CI 1.01 to 2.20). Living near the harbour was associated with higher mortality from lung cancer (HR=1.31, 95% CI 1.04 to 1.66) and neurological diseases (HR=1.51, 95% CI 1.05 to 2.18). Conclusions: Estimated exposures to different pollution sources in this area were independently associated with several mortality outcomes while adjusting for occupation and socioeconomic status.